Robert Ludlum's The Bourne ascendancy [compact disc, unabridged] : a new Jason Bourne novel - Lustbader, Eric (Lustbader, Eric. New Jason Bourne novel., 2014)
Jason Bourne is now someone who is hired by high-level government ministers to impersonate them at meetings with uncertain security. Bourne is at one such meeting when armed gunmen storm the room after Bourne himself. Kidnapped and transported to an underground bunker, Bourne finds himself face-to-face with a well-known terrorist, a man who calls himself El Ghadan. He demands that Bourne carry out a special mission for him that, if completed, will have dire consequences for the entire world.